Potensi Tradisi Ngejot Sebagai Sumber Belajar PPKn - Riki Azwari; Muh. Zubair; Sawaludin Sawaludin; Yuliatin Yuliatin (Faculty of training and education, Pamulang university, 2022)
This study aims to determine: (1) the implementation of the ngejot tradition in Lenek Pesiraman Village; (2) the character values contained in the implementation of the ngejot tradition in Lenek Pesiraman Village; (3) The Potential of the Ngejot Tradition as a Learning Source for Civics subjects. The approach used is a qualitative approach with ethnographic research. Data collection techniques used are observation, interviews and documentation. The data analysis technique used the Miles and Huberman analysis technique. The results showed that the implementation of the ngejot tradition had several stages, namely the Preparation, Implementation and Closing stages. The preparation stage consists of deliberation and preparing ritual materials. The implementation stage consists of ngatong dulang (bringing trash), uduk (taking ablution water), nyadek jot-jotan (giving jot-jotan). The Closing Stage consists of prayer. The character values contained in the ngejot tradition in Lenek Pesiraman Village are Democratic, Religious, Peace-loving, Responsibility and care for the environment. The ngejot tradition has the potential to be a source of PPKn learning, namely in aspects of education related to learning materials based on the 2013 curriculum because of the requirements for character values in it that can shape the character of students in order to maintain cultural diversity.Keywords: Ngejot; Character Values; PPKn Learning Resources;